Magnesium impacts myosin V motor activity by altering key conformational changes in the mechanochemical cycle - Trivedi, Darshan (2013)
We investigated how magnesium (Mg) impacts key conformational changes during the ADP binding/release steps in myosin V and how these alterations impact the actomyosin mechanochemical cycle. The conformation of the nucleotide binding pocket was examined with our established FRET system in which myosin V labeled with FlAsH in the upper 50 kDa domain participates in energy transfer with mant labeled nucleotides. We examined the maximum actin-activated ATPase activity of MV FlAsH at a range of free Mg concentrations (0.1–9 mM) and find that the highest activity occurs at low Mg (0.1–0.3 mM), while there is a 50–60% reduction in activity at high Mg (3–9 mM). The motor activity examined with the in vitro motility assay followed a similar Mg-dependence and the trend was similar with dimeric myosin V. Transient kinetic FRET studies of mantdADP binding/release from actomyosin V FlAsH demonstrate that the transition between the weak and strong actomyosin. ADP states is coupled to movement of the upper 50 kDa domain and is dependent on Mg with the strong state stabilized by Mg. We find that the kinetics of the upper 50 kDa conformational change monitored by FRET correlates well with the ATPase and motility results over a wide range of Mg concentrations. Our results suggest the conformation of the upper 50 kDa domain is highly dynamic in the Mg free actomyosin. ADP state, which is in agreement with ADP binding being entropy driven in the absence of Mg. Overall, our results demonstrate that Mg is a key factor in coupling the nucleotide- and actin-binding regions. In addition, Mg concentrations in the physiological range can alter the structural transition that limits ADP dissociation from actomyosin V, which explains the impact of Mg on actin-activated ATPase activity and in vitro motility.